2008
DOI: 10.1037/0278-6133.27.3(suppl.).s260
|View full text |Cite
|
Sign up to set email alerts
|

Getting there and hanging on: The effect of regulatory focus on performance in smoking and weight loss interventions.

Abstract: A fit between behavioral task and regulatory focus can facilitate the successful performance of meaningful behaviors over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 31 publications
5
49
1
2
Order By: Relevance
“…A promotion-focused individual who is more open to change, pays more attention to innovatory characteristics and buys more new products than a prevention-focused consumer (Herzenstein, Posavac, and Brakus 2007). A promotion-focused individual, driven by his or her eagerness to reach the final desired state, changes his or her behaviour relatively easily, whereas a prevention-focused individual who is anxious to carefully maintain a desired state, is more likely to continue his or her current behaviour in the long term (Fuglestad, Rothman, and Jeffery 2008).…”
Section: Promotion Focus Prevention Focus and Store Loyaltymentioning
confidence: 96%
“…A promotion-focused individual who is more open to change, pays more attention to innovatory characteristics and buys more new products than a prevention-focused consumer (Herzenstein, Posavac, and Brakus 2007). A promotion-focused individual, driven by his or her eagerness to reach the final desired state, changes his or her behaviour relatively easily, whereas a prevention-focused individual who is anxious to carefully maintain a desired state, is more likely to continue his or her current behaviour in the long term (Fuglestad, Rothman, and Jeffery 2008).…”
Section: Promotion Focus Prevention Focus and Store Loyaltymentioning
confidence: 96%
“…If the RFQ assesses a construct more closely aligned with external vs. internal motivations than with health preventive vs. promoting motivations (Summerville and Roese, 2008), its use may explain the emergence of counter-intuitive findings. Another such finding is that promotion (i.e., internal motivated) focus is associated with health behavior initiation, whereas prevention (i.e., external motivated) focus is associated with maintenance (Fuglestad, et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Emerging research has suggested interventions target and frame messages about how people reach goals in their life, such as sustained weight loss, through either a prevention or promotion focus; this is known as regulatory focus theory [46]. This may be beneficial by motivating people to self-regulate and sustain recent behavioral changes [47] such as weight control [48]. This may be particularly useful at the continued response phase of the behavior change process.…”
Section: Introductionmentioning
confidence: 99%